Development and Assessment of a Color-Variable Chlorine Dioxide Slow-Releasing Card for Litchi Preservation - Li Guo; Guang Wu; Qingchun Yin; Lin Luo; Hao Deng (Foods)
Chlorine dioxide (ClO2) gas has attracted considerable attention due to its safety and efficiency. In this study, we successfully developed a color-variable ClO2 slow-releasing card for postharvest litchi. The optimal ClO2 slow-releasing card was prepared as follows: Card A was soaked in 2.5 mol/L NaClO2 and 0.3 mol/L CaCl2. Card B was soaked in 1 mol/L oxalic acid, 0.3 mol/L CaCl2, and natural pigment. Finally, cards A and B were dried and adhered using 60% gelatin. The ClO2 releasing time of the card was more than 120 h at 5–25 °C, and it could change color from dark yellow to white. The qualities of 3 kg litchi treated with no pieces (CK), half a piece (T1), one piece (T2), two pieces (T3), and three pieces (T4) of ClO2 slow-releasing card were compared. The results showed that litchi of T1 had significantly (p < 0.05) higher L* and a* values but a lower respiration rate and relative conductivity than CK after 7 days of storage, showing the best pulp qualities and pericarp color. Further correlation analyses revealed a significant positive correlation (R2 = 0.971) between Cya-3-O-gal-1 and a*, indicating a sharp decline in Cya-3-O-gal-1 and strong pericarp browning in CK. On the contrary, the low-releasing ClO2 of T1 effectively inhibited Cya-3-O-gal-1 degradation. This could be one of the reasons for the superior pericarp color of T1. This study provides a visual, efficient, and economical solution for postharvest litchi.